Teachers’ Virtual Education Experiences in Iraq: Insights from a Mixed-Methods Study on Challenges and Consequences - ABBAS TAHER ALLAWI GHRABAT; NASROLAH GHASHGHAEIZADEH; JALAL SHANTA JABER; FRANK MOSAVI (Journal of Advances in Medical Education and Professionalism)
Introduction: The COVID-19 pandemic has significantly transformed the educational landscape in Iraq, necessitating a rapid shift from traditional classroom settings to virtual education. This study aimed to examine the experiences of Arabic virtual education teachers in Iraq, with a focus on the challenges they faced and the implications of adopting online teaching methodologies.Methods: A mixed-methods approach was applied, incorporating a qualitative-quantitative approach for tool development. The qualitative section dealt with content analysis, while the quantitative section followed a descriptive survey method. The study was performed in 2023. The qualitative sampling was purposeful, involving 15 experts in virtual education from Iraq, whereas the quantitative samples consisted of 368 teachers from 20 schools in Baghdad, Iraq, selected via cluster sampling. The qualitative tool was a semi-structured interview, whereas the quantitative tool was a researcher-made questionnaire consisting of 10 components and 66 items. For data analysis, exploratory factor analysis was carried out. The data were analyzed using SPSS 22 software.Results: A total of 15 educational experts contributed to the qualitative analysis, while the opinions of 398 teachers were inspected through exploratory factor analysis for content analysis. The sample’s adequacy and the test’s suitability were validated using two indicators: Kaiser-Meyer-Olkin (KMO=0.684) and Bartlett’s Test of Sphericity, both being significant at >0.001. Thequantitative findings presented the extraction of 10 factors, which accounted for 85.823% of the total variance at the eigenvalue point. These factors included Utility (9 items), Implications (8 items), Flexibility and Adaptability (7 items), Equity (7 items), Balanced Infrastructure Development (7 items), Evaluation and Motivation Mechanisms (6 items), Management and Policy Making (8 items), Awareness and Empowerment (6 items), Educational Planning (4 items), and Technology Enhanced Learning (3 items).Conclusion: The findings highlight the complex challenges encountered by Iraqi educators in virtual learning environments, underscoring the significance of addressing infrastructural gaps,providing adequate training, and fostering equitable access to technology. By focusing on these domains, educational stakeholders can boost the effectiveness of online education in Iraq, ultimately improving educational outcomes for all students.